TMEM163 Regulates ATP-Gated P2X Receptor and Behavior - Elizabeth J. Salm; Patrick J. Dunn; Lili Shan; Miwako Yamasaki; Nathalie M. Malewicz; Taisuke Miyazaki; Joongkyu Park; Akio Sumioka; R. Richard L. Hamer; Wei-Wu He; Megumi Morimoto-Tomita; Robert H. LaMotte; et al. (Cell Reports, 2020)
Summary: Fast purinergic signaling is mediated by ATP and ATP-gated ionotropic P2X receptors (P2XRs), and it is implicated in pain-related behaviors. The properties exhibited by P2XRs vary between those expressed in heterologous cells and in vivo. Several modulators of ligand-gated ion channels have recently been identified, suggesting that there are P2XR functional modulators in vivo. Here, we establish a genome-wide open reading frame (ORF) collection and perform functional screening to identify modulators of P2XR activity. We identify TMEM163, which specifically modulates the channel properties and pharmacology of P2XRs. We also find that TMEM163 is required for full function of the neuronal P2XR and a pain-related ATP-evoked behavior. These results establish TMEM163 as a critical modulator of P2XRs in vivo and a potential target for the discovery of drugs for treating pain.